Effect of fat replacement with different types of eggplants on the physicochemical and sensorial properties of chicken sausages: a chemometric approach - Hamidon, Farra Nabilah; Faridah, Mohd Razali; Asyrul-Izhar, Abu Bakar; Abdullah Sani, Muhamad Shirwan; Ismail-Fitry, Mohammad Rashedi (Malaysian Analytical Sciences Society, 2022)
Animal fat plays an important role in processed meat products as it is responsible for improving some physicochemical and sensorial qualities of the final products. However, consumption of high-fat food products is linked to a higher risk of various cardiometabolic diseases such as type 2 diabetes mellitus and cardiovascular diseases. Eggplant has the potential to be used as a fat replacer, but different types of eggplants could produce various results. Thus, this study aimed to produce reduced-fat chicken sausages re-formulated with five different types of eggplants [Round Asian Eggplant (RAE), Pearl Red Eggplant (PRE), Pea Eggplant (PE), Round Black Eggplant (RBE), and Green Thai Eggplant (GTE)] as the fat replacers. The chicken sausages were evaluated for physicochemical and sensorial properties and compared to sausage containing only chicken fat as the control. The RAE, PRE, and PE sausages had the lowest fat content at 4.34%, 6.30% and 7.64%, respectively, thus can be claimed as reduced fat chicken sausages. There were no significant differences among all formulations in terms of ash, moisture, protein, cooking loss, water holding capacity, springiness, and cohesiveness. The sensory analysis revealed that consumers accepted the RAE and PRE sausages compared to the control and the least preferred was PE. This was supported by the PCA, which positively proposed lower fat content (4.34%) and higher a* value (3.21) while rejecting higher pH (6.35) and b* values (15.88) of the reduced-fat-chicken sausages. In conclusion, eggplants can be used as fat replacers to produce reduced-fat chicken sausages with Round Asian Eggplant being the best option.